2020
DOI: 10.1007/s10950-020-09921-8
|View full text |Cite
|
Sign up to set email alerts
|

Seiscloud, a tool for density-based seismicity clustering and visualization

Abstract: Clustering algorithms can be applied to seismic catalogs to automatically classify earthquakes upon the similarity of their attributes, in order to extract information on seismicity processes and faulting patterns out of large seismic datasets. We describe here a Python open-source software for density-based clustering of seismicity named seiscloud, based on the pyrocko library for seismology. Seiscloud is a tool to dig data out of large local, regional, or global seismic catalogs and to automatically recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…The most interesting result of the MT inversion is that it demonstrates a high variability of MT configurations and faulting style over a quite compact region, extending laterally less than 60 km (Figures 1 and 5). Most of the 102 MT solutions could be classified (Cesca, 2020; see Figure S5) into eight families, each sharing similar focal mechanisms, spanning from pure strike-slip to pure thrust, and normal faulting. The variability in these mechanisms is consistent with a NE-SW trending pressure axes, in agreement with the convergence direction, and a NW-SE tension axis (Figure 5c).…”
Section: Earthquake Focal Mechanismsmentioning
confidence: 99%
“…The most interesting result of the MT inversion is that it demonstrates a high variability of MT configurations and faulting style over a quite compact region, extending laterally less than 60 km (Figures 1 and 5). Most of the 102 MT solutions could be classified (Cesca, 2020; see Figure S5) into eight families, each sharing similar focal mechanisms, spanning from pure strike-slip to pure thrust, and normal faulting. The variability in these mechanisms is consistent with a NE-SW trending pressure axes, in agreement with the convergence direction, and a NW-SE tension axis (Figure 5c).…”
Section: Earthquake Focal Mechanismsmentioning
confidence: 99%
“…We used a clustering algorithm (Cesca, 2020) based on the Kagan angles between all focal mechanisms obtained in this study and reported by gCMT, GEOFON, INGV, SED, EM-RCMT and ARSO to define classes of similar mechanisms (Fig. 9).…”
Section: Dominant Mechanisms and The Regional Stress Regimementioning
confidence: 99%
“…For the detection of spatial earthquake clusters, we use a density-based clustering algorithm (Cesca et al 2014;Maghsoudi et al 2013;Cesca 2020). The method scans the hypocentral distribution of the CSN catalogue, searching for regions with high earthquake density to detect seismicity clusters:…”
Section: Spatial Distribution Of Seismicity Clustersmentioning
confidence: 99%
“…The definition of clustering parameters has been chosen with the objective to simultaneously resolve a limited number of clusters and reduce as much as possible the amount of unclustered events (Cesca 2020).…”
Section: Spatial Distribution Of Seismicity Clustersmentioning
confidence: 99%
See 1 more Smart Citation